Agroforestry systems conserve species-rich but modified assemblages of tropical birds and bats - Harvey, Celia (2007)
Although an increasing number of studies have shown that diverse, multi-strata agroforestry systems can contribute to the conservation of tropical biodiversity, there is still debate about how the biodiversity within agroforestry systems compares to that of intact forest and alternative land uses. In order to assess the relative importance of agroforestry systems for biodiversity conservation, we characterized bat and bird assemblages occurring in forests, two types of agroforestry systems (cacao and banana) and plantain monocultures in the indigenous reserves of Talamanca, Costa Rica. A total of 2,678 bats of 45 species were captured, and 3,056 birds of 224 species were observed. Agroforestry systems maintained bat assemblages that were as (or more) species-rich, abundant and diverse as forests, had the same basic suite of dominant species, but contained more nectarivorous bats than forests. Agroforestry systems also contained bird assemblages that were as abundant, species-rich and diverse as forests; however the species composition of these assemblages was highly modified, with fewer forest dependent species, more open area species and different dominant species. The plantain monocultures had highly modified and depauperate assemblages of both birds and bats. Across land uses, bird diversity and species richness were more closely correlated with the structural and floristic characteristics than were bats, suggesting potential taxon-specific responses to different land uses. Our results indicate that diverse cacao and banana agroforestry systems contribute to conservation efforts by serving as habitats to high numbers of bird and bat species, including some, but not all, forest-dependent species and species of known conservation concern. However, because the animal assemblages in agroforestry systems differ from those in forests, the maintenance of forests within the agricultural landscape is critical for conserving intact assemblages at the landscape level.